Influence of obesity on incidence of thrombosis and disease severity in patients with COVID-19: From the CLOT-COVID study. Issue 1 (January 2023) - Ogihara, Yoshito; Yachi, Sen; Takeyama, Makoto; Nishimoto, Yuji; Tsujino, Ichizo; Nakamura, Junichi; Yamamoto, Naoto; Nakata, Hiroko; Ikeda, Satoshi; Umetsu, Michihisa; Aikawa, Shizu; Hayashi, Hiroya; et al.
Abstract: Background: The influence of obesity on the development of thrombosis and severity of coronavirus disease 2019 (COVID-19) remains unclear. Method: The CLOT-COVID study was a retrospective multicenter cohort study enrolling 2894 consecutive hospitalized patients with COVID-19 between April 2021 and September 2021 among 16 centers in Japan. The present study consisted of 2690 patients aged over 18 years with available body mass index (BMI), who were divided into an obesity group (BMI ≥30) ( N  = 457) and a non-obesity group (BMI <30) (N = 2233). Results: The obesity group showed more severe status of COVID-19 at admission compared with the non-obesity group. The incidence of thrombosis was not significantly different between the groups (obesity group: 2.6 % versus non-obesity group: 1.9 %, p  = 0.39), while the incidence of a composite outcome of all-cause death, or requirement of mechanical ventilation or extracorporeal membrane oxygenation during hospitalization was significantly higher in the obesity group (20.1 % versus 15.0 %, p  < 0.01). After adjusting confounders in the multivariable logistic regression model, the risk of obesity relative to non-obesity for thrombosis was not significant (adjusted OR, 1.39; 95 % CI, 0.68–2.84, p  = 0.37), while the adjusted risk of obesity relative to non-obesity for the composite outcome was significant (adjusted OR, 1.85; 95 % CI, 1.39–2.47, p  < 0.001). Conclusions: In the present large-scale observational study, obesity was not significantly associated with the development of thrombosis during hospitalization; however, it was associated with severity of COVID-19. Graphical abstract: Unlabelled Image Highlights: The association between obesity and thrombosis remains unclear. We investigated the influence of obesity on thrombosis and severity of coronavirus disease 2019 (COVID-19). Obesity was associated with severe status of COVID-19. Obesity did not significantly confer risk of developing thrombosis in COVID-19.